Zooarchaeology and ancient DNA, part 2: new substrates and perspectives - Lebrasseur, O; Manin, A (A.Kh. Khalikov Archaeology Institute of the Academy of Sciences of Tatarstan, 2021)
The last decade has seen important technological and methodological advances in the field of palaeogenomics, constantly pushing back the time boundary and broadening our understanding of past human-animal interactions. As well as the development of sequencing technologies, a variety of organic material is being (re)evaluated as potential substrates for DNA analyses. The authors here review a selection of these, including collagenous (leather and parchment), keratinous (hair and feather) and calcified (shell and eggshell) material, and environmental DNA including coprolite. The authors focus on the biological structure of these materials in relation to DNA preservation, highlighting their singularity in comparison to bones and teeth, and inform on some of their direct applications. Finally, the authors consider some of the new perspectives these substrates can bring to our understanding of the past, notably surrounding manufacturing practices and health.